Sodium‐Glucose Cotransporter 2 Inhibition for the Prevention of Cardiovascular Events in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta‐Analysis. Issue 3 (4th February 2020) - Arnott, Clare; Li, Qiang; Kang, Amy; Neuen, Brendon L.; Bompoint, Severine; Lam, Carolyn S. P.; Rodgers, Anthony; Mahaffey, Kenneth W.; Cannon, Christopher P.; Perkovic, Vlado; Jardine, Meg J.; Neal, Bruce
Abstract : Background: Several trials have demonstrated protective effects from inhibition of sodium‐glucose cotransporter 2 among patients with type 2 diabetes mellitus. There is uncertainty about the consistency of the cardiovascular benefits achieved across patient subsets. Methods and Results: We included 4 large‐scale trials of sodium‐glucose cotransporter 2 inhibition compared with placebo in patients with diabetes mellitus that reported effects on cardiovascular outcomes overall and for participant subgroups defined at baseline by cardiovascular disease, reduced kidney function, and heart failure. Fixed effects models with inverse variance weighting were used to estimate summary hazard ratios and 95% CIs. There were 38 723 patients from 4 trials, with a mean 2.9 years of follow‐up. Of the patients, 22 870 (59%) had cardiovascular disease, 7754 (20%) had reduced kidney function, and 4543 (12%) had heart failure. There were 3828 major adverse cardiac events. There was overall benefit for major adverse cardiac events (0.88; 95% CI, 0.82–0.94; P <0.001) and no evidence that the effects of sodium‐glucose cotransporter 2 inhibition varied across patient subgroups, defined by the presence of cardiovascular disease or heart failure at baseline (all P interaction >0.252; I 2 <25%). All patient subgroups benefited with respect to hospitalization for heart failure (all P interaction>0.302; I 2 <10%), cardiovascular death (all P interaction>0.167; I 2 <50%), and death from any cause (all P interaction>0.354; I 2 =0%). The only difference in effects across subgroups was for stroke, with protection observed among those with reduced kidney function but not those with preserved kidney function ( P interaction=0.020; I 2 =81%). Conclusions: Sodium‐glucose cotransporter 2 inhibitors protect against cardiovascular disease and death in diverse subsets of patients with type 2 diabetes mellitus regardless of cardiovascular disease history.